Pengaruh Model Problem Based Learning (PBL) Berbasis Etnosains Pada Konsep "Teknologi Tradisional" Terhadap Kemampuan Kolaborasi Peserta Didik Kelas V - Qorina, Maylan; Andriana, Encep; Syachruroji, A. (Jurnal Pendidikan : Riset dan Konseptual, 2025)
With the backdrop of students' poor cooperation abilities during discussion activities, This study aims to determine how students' collaborative abilities in IPAS learning are affected by the ethnoscientific Problem Based Learning (PBL) paradigm. This study employs a quantitative research technique with a quasi-experimental approach and a nonequivalent control group design. A collaboration ability questionnaire that doubles as a pretest and a posttest is the research instrument used in this study. Among the techniques used for data analysis are ANOVA, MANOVA, homogeneity, and the normalcy test. The results of the study indicate that the Problem Based Learning (PBL) methodology can enhance students' capacity for teamwork, as evidenced by an increase in scores from 73.32 to 75.66. However, when learning is conducted using the cooperative model Think-Pair-Share, the initial score of 64.77 significantly increased to 71.28. Therefore, when compared to learning using the Think-Pair-Share cooperative model, Students' ability to collaborate Utilizing the Problem Based Learning (PBL) paradigm can enhance.